2021
DOI: 10.1108/jfmpc-03-2021-0022
|View full text |Cite
|
Sign up to set email alerts
|

Attributes and impact of advance payment system on cash flow, project and organisational performance

Abstract: Purpose Construction companies require meticulous and thorough financial planning to ensure business survival in an increasingly competitive global market. Past studies assert that cash flow management is also crucial to meeting project and organisational performance expectations. However, the link between an advance payment system (APS), cash flow and project performance has hitherto received scant academic attention. Therefore, this study aims to investigate the attributes and impact of APS on cash flow, pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 56 publications
0
22
0
2
Order By: Relevance
“…This study is underpinned by the positivist philosophical stance (Saunders et al, 2015;Edwards et al, 2019). Positivism is an epistemological stance which is linked to the philosophical position of the natural scientist and includes dealing with observable social reality to develop law-like generalisations (Omopariola et al, 2021). Positivists employ deductive, structured, large samples, measurement and typically adopt quantitative methods (Saunders et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study is underpinned by the positivist philosophical stance (Saunders et al, 2015;Edwards et al, 2019). Positivism is an epistemological stance which is linked to the philosophical position of the natural scientist and includes dealing with observable social reality to develop law-like generalisations (Omopariola et al, 2021). Positivists employ deductive, structured, large samples, measurement and typically adopt quantitative methods (Saunders et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…, 2019). Positivism is an epistemological stance which is linked to the philosophical position of the natural scientist and includes dealing with observable social reality to develop law-like generalisations (Omopariola et al. , 2021).…”
Section: Methodsmentioning
confidence: 99%
“…This strategy is essential as the injection of financing at set intervals enables the ongoing advancement of a construction project in the form of material and labour expenditures, culminating in timely project delivery. Still the phenomena of delayed payments, and cash flows from client to contractors, do not possess a simple solution of paying on time at set intervals [5]. The challenges associated with obtaining continuous project finances are a global concern and impede project completion by placing undue financial strain on contractors and project stakeholders.…”
Section: Introductionmentioning
confidence: 99%
“…However, different payment systems apply to different project environments and expectations given that each construction project is bespoke in terms of the project's specifications and procurement arrangement (the so-called 'project environment') (Omopariola and Windapo, 2018). Omopariola and Windapo (2018) posit that construction projects fail to deliver as expected due to a mismatch between payments systems used on a project environment. Scott and Mitchell (2017) proffer that when an appropriate payment method or system is used (and in the best-fit project environment), the effectiveness of that project and concomitant organisational performance will improve.…”
Section: Introductionmentioning
confidence: 99%
“…The study's conclusion (Omopariola and Windapo, 2019) was tentative and indicated that APS has no effect on project cash flow and the performance of organisations and projects. Also, Omopariola et al (2022) investigated the impact of attributes of an APS on cash flow, project and organisational performance. The study (Omopariola et al, 2022) concluded that APS serves as an effective payment system that can catalyse the performance of organisations and projects towards construction operations success.…”
Section: Introductionmentioning
confidence: 99%